Meta-Analysis the Effects of Social Isolation and Loneliness on Cardiovascular Disease and Death in Elderly - Ayu Novita Wulandari; Bhisma Murti; Didik Tamtomo (Masters Program in Public Health, 2023)
Background: The impact of social isolation and loneliness on health and well-being is recognized globally as a public health problem. Social isolation can be experienced at any age, especially the elderly. This study aims to analyze and estimate the influence of social isolation and loneliness on cardiovascular disease and death in the elderly.Subjects and Method: The meta-analysis was carried out according to the PRISMA flow chart and the PICO model. P: Elderly, I: Social isolation and loneliness, C: Not social isolation and not lonely, O: Cardiovascular disease and death. Search for articles in this study through databases that include PubMed, Google Scholar, Science Direct and Scopus with keywords